Impact of Rest and Secondary Intervention on Musculoskeletal Disorder Development, Systemic Inflammation and Sensorimotor Behavioral Declines in A Rat Model. (November 2019) - Smith, Tianqi Tenchi Gao; Barr-Gillespie, Ann E; Harris, Michelle; Amin, Mamta; Gallagher, Sean; Barbe, Mary Frances
Background: Musculoskeletal Disorders (MSDs) are prevalent at occupational settings. It has been shown previously that chronic performance of high-force-high-repetition (HFHR) tasks lead to significantly elevated systemic inflammation, nerve pain and decreased sensorimotor outcomes in a rat model. This study examined rest and a secondary intervention method, flat treadmill running's potential remedial effects on the abovementioned negative outcomes.Methods: Young adult female Sprague-Dawley rats were trained to perform a high-force reaching task. The trained rats were then randomly assigned with rest or no rest, to perform a HFHR reaching and pulling task for 10 weeks either with or without treadmill intervention. Outcomes including sensorimotor behavior, serum cytokine levels, number of activated macrophages in median nerve, forepaw mechanical sensitivity, Bonar scores of flexor tendon histomorphology were collected and compared to control rats.Results: Rest attenuated task-induced mechanical sensitivity, and cytokine levels, tendon cellularity, yet did not improve reflexive grip strength. Treadmill running attenuated increases several serum cytokines and chemokines, as well as tendon cellularity due to HFHR task, yet worsened several sensorimotor outcomes, macrophage count in median nerve, and forepaw mechanical sensitivity.Conclusion: Both rest and intervention remedied the MSDs induced by the HFHR task in chronic tendon morphology but not in all outcomes measured. Treadmill intervention worsened pain and discomfort experienced in forepaws and median nerve, as well as systemic inflammation level likely due to the intervention mechanism's intensity and its continual loading to the injured limbs.